Regional developments [in 2023 Global Food Policy Report] - Benin, Samuel; Marivoet, Wim; Mawia, Harriet; Ulimwengu, John M.; Abay, Kibrom A.; Diao, Xinshen; Laborde Debucquet, David; Raouf, Mariam; Akramov, Kamiljon T.; Kumar, Anjani; Rashid, Shahidur; Chen, Kevin Z.; et al. (International Food Policy Research Institute, 2023)
Recent global crises have led to diverse impacts across the world’s low- and middle-income regions, reflecting local conditions and differing policy responses. These effects are often compounded by more local shocks and crises, including prolonged conflict and violence, natural disasters, and fragile economic and governance systems. This section examines the impacts of recent food crises to identify both future risks and promising policy options that could improve early warning, immediate response, and resilience building in each region.